Land use Conflict in Gunung halimun Salak National Park Lebak District - Hakim, Nurman; Murtilaksono, Kukuh (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2016)
ABSTRACTDevelopment for conservation, agriculture and settlements have equal importance for humankind. Reality showed, conflict is occured because of each goal use its own knowledge and values. The conflict was found in the forest area of Gunung Halimun Salak National Park. The study aimed to identify the landuse conflict between conservation with agriculture, settlement, include mining, and identify the strategic issues that arised from the conflict. This study was conducted in Gunung Halimun Salak National Park at Lebak regency. The study using qualitative and quantitative approach. Spatial multicriteria analysis was employed to identify the areas of conflict. List of issue derived from three sources: observing landuse conflict map, discussion with the expert and stakeholder’s strategic document. The strategic issues is classifyed based on level of agreement among experts.The result showed that conflict which had been occurred between conservation and agriculture of 22,061.11 ha (49%); between conservation and settlement of 1,830.36 Ha (4%); and between conservation and mining of 26,007.86 Ha (58 %). Analysis of strategic issues leads to 11 issues were grouped to three agendas, namely (1) Tenure and environmental damage, (2) disaster mitigation and food security, and (3) infrastructure development for agriculture and settlement.Keywords: Gunung Halimun Salak district Lebak, landuse conflict, landuse preferences, multicriteria analysis.ABSTRAKPembangunan untuk tujuan konservasi, pertanian dan permukiman memiliki nilai penting yang setara demi kesejahteraan manusia. Kenyataan menunjukan bahwa ketiga tujuan tersebut kerap berbenturan dan menimbulkan konflik karena masing-masing menggunakan pengetahuan dan nilainya sendiri-sendiri. Konflik tersebut dijumpai di kawasan hutan Taman Nasional Gunung Halimun Salak. Penelitian ini bertujuan untuk mengidentifikasi konflik penggunaan lahan antara konservasi dengan pertanian, permukiman termasuk pertambangan, serta mengidentifikasi isu strategis yang muncul dari konflik yang terjadi. Penelitian dilakukan di kawasan hutan Taman nasional Gunung Halimun salak di Kabupaten Lebak. Penelitian ini menggunakan kombinasi pendekatan kualitatif dan kuantitatif. Analisis spasial multikriteria digunakan untuk mendeskripsikan area-area yang mengalami konflik. Isu-isu digali dari pengamatan peta konflik, wawancara narasumber ahli dan kajian dokumen strategis. Perumusan isu strategis didasarkan pada tingkat kesepakatan diantara para narasumber. Hasil penelitian memperlihatkan terjadi konflik penggunaan lahan antara konservasi dengan pertanian seluas 22.061,11 ha (49%); antara konservasi dengan permukiman seluas 1.830,36 Ha (4%); dan antara konservasi dengan pertambangan seluas 26.007,86 Ha (58 %). Terdapat 11 isu strategis yang dirumuskan menjadi 3 kelompok isu dan diajukan sebagai agenda bersama pengelolaan konflik penggunaan lahan, yaitu: (1) Isu lingkungan dan penyelesaian tenurial, (2) Isu mitigasi bencana dan ketahanan pangan, dan (3) Isu pengembangan infrastuktur pertanian dan permukiman.Kata kunci: TNGHS Kabupaten Lebak, konflik penggunaan lahan, preferensi penggunaan lahan, analisis multikriteria.